MINISTERIAL FORMATION FOR SERVICE: INTEGRATIVE THEOLOGICAL EDUCATION AT JUSTO MWALE UNIVERSITY, ZAMBIA - D.T. Banda; L. Banda; M. Blok; M. Naidoo (Acta Theologica)
In ministerial training, effective integration of academic excellence, spiritual formation and vocational training is critical to produce holistically trained Christian leaders. This article positions integration as an educational approach that attempts to coordinate and synthesise the major learning dimension and can bring about significant learning, since it takes account of the lifeworld of the student and engages a custom-designed curriculum. This article reports on an empirical research project on integrative theological education at Justo Mwale University, Zambia. It reports on various dimensions within the formal and informal curriculum in the residential Bachelor of Theology programme. The article provides key findings and a discussion on the contextual and institutional challenges that shaped curriculum design. It reflects on the learning gained through this action research and concludes with strategies to move towards a more integrative model of theological education.